Death Associated Protein Kinase 1 (DAPK1): A Regulator of Apoptosis and Autophagy - Singh, Pratibha; Ravanan, Palaniyandi; Talwar, Priti (Frontiers in Molecular Neuroscience, 2016)
Death-Associated Protein Kinase 1 (DAPK1) belongs to a family of five serine/threonine kinases that possess tumor suppressive function and also mediate a range of cellular processes, including apoptosis and autophagy. The loss and gain-of–function of DAPK1 is associated with various cancer and neurodegenerative diseases respectively. In recent years, mechanistic studies have broadened our knowledge of the molecular mechanisms involved in DAPK1-mediated autophagy/apoptosis. In the present review we have discussed structural information and various cellular functions of DAPK1 in a comprehensive manner.